2014
DOI: 10.1016/j.bbmt.2013.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Back to the Future! The Evolving Role of Maintenance Therapy after Hematopoietic Stem Cell Transplantation

Abstract: Relapse is a devastating event for patients with hematologic cancers treated with hematopoietic stem cell transplantation. In most situations, relapse treatment options are limited. Maintenance therapy offers the possibility of delaying or avoiding disease recurrence, but its role remains unclear in most conditions we transplant. Here, Dr. Hourigan presents an overview of minimal residual disease (MRD) measurement in hematologic malignancies and the applicability of MRD-based post-transplant interventions. Dr.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 107 publications
(97 reference statements)
0
19
1
Order By: Relevance
“…(1315) They showed that azacitidine (AZA) can be safely administered to heavily pretreated post-transplant patients and may prolong event-free and overall survival. In addition, recent studies have shown that AZA, followed by DLI, is well tolerated when administered for early AML/MDS relapse after alloHSCT.…”
Section: Introductionmentioning
confidence: 99%
“…(1315) They showed that azacitidine (AZA) can be safely administered to heavily pretreated post-transplant patients and may prolong event-free and overall survival. In addition, recent studies have shown that AZA, followed by DLI, is well tolerated when administered for early AML/MDS relapse after alloHSCT.…”
Section: Introductionmentioning
confidence: 99%
“…The use of post-transplant therapy after ASCT is attractive. 48 Maintenance therapy post ASCT was introduced in adult ALL by the Royal Marsden team in the UK; 27 of 71 patients in CR 120 days after ASCT, those receiving two or three maintenance agents had significantly lower RI and superior LFS compared with those receiving one or none. In the Russian ALL study group, 40 which used the BEAM regimen in patients with ALL who underwent ASCT in CR1, patients also received maintenance therapy for 2 years post transplant.…”
mentioning
confidence: 99%
“…The “number needed to test” for cost-neutrality would likely be highly favorable given the considerable economic consequences of preventing an inappropriate transplant for example. Furthermore, given the rising costs of drug development and efficiency in the conduct of clinical trials required for drug approval [71] and increased focus on targeted relapse prevention with maintenance therapy [72] having quantifiable evidence of efficacy for interventions performed in the remission setting is likely to have benefit.…”
Section: What Are the Constraints That Impact Aml Mrd And Its Adoptiomentioning
confidence: 99%